Lipid Nanoparticle and Liposome Reference Materials Assessment of Size Homogeneity and Long-Term -70 °C and 4 °C Storage Stability - Jakubek, Zygmunt J (Langmuir : the ACS journal of surfaces and colloids, 2023)
With recent advances and anticipated proliferation of lipid nanoparticle (LNP)-delivered vaccines and therapeutics, there is a need for the availability of internationally recognized reference materials of LNP systems. Accordingly, we developed six LNP and liposome (anionic, neutral, and cationic each) candidate reference material formulations and thoroughly characterized by dynamic light scattering their particle hydrodynamic size (Z-avr) and polydispersity. We also evaluated the particle size homogeneity and long-term -70 °C and 4 °C storage stability using multiple large sets of randomly selected vials for each formulation. The formulations stored at -70 °C remained stable and homogeneous for a minimum of 9 months. The Z-avr relative combined uncertainty and the long-term variability were both <1.3% for liposome formulations and anionic LNPs, (3.9% and 1.7%) for neutral LNPs, and (6.7% and 4.4%) for cationic LNPs. An inadvertent few-hour-long storage temperature increase to -35 °C due to a freezer malfunction resulted in a small change of the size and size distribution of anionic liposomes and LNPs but, unexpectedly, a larger size increase of the neutral and cationic liposomes (≤5%) and LNPs (≤25%). The mean Z-avr values of the LNPs stored at 4 °C appeared to slowly increase with t1/3, where t is the storage time, and the Z-avr between-vial heterogeneity and mean polydispersity index values appeared to decrease; no change was observed for liposomes. The size and size distribution evolution of LNPs stored at 4 °C was attributed to an incomplete equilibration of the formulations following the addition of sucrose prior to the initial freezing. Such a process of size increase and size distribution narrowing has not been previously discussed nor observed in the context of LNPs